2008
DOI: 10.1088/0031-8949/79/01/015701
|View full text |Cite
|
Sign up to set email alerts
|

Band parameters for AlAs, InAs and their ternary mixed crystals

Abstract: The electronic, optical and mechanical properties of AlAs, InAs and their mixed crystals Al 1−x In x As are studied within the empirical pseudopotential approach under the virtual crystal approximation. To make allowance for the compositional disorder, a correction to the alloy potential has been introduced. The results are presented and compared where possible with other calculations and experimental data. The composition dependence of the selected features of Al 1−x In x As, such as energy band gaps, valence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(11 citation statements)
references
References 33 publications
2
9
0
Order By: Relevance
“…Therefore, alu min iu m arsenide has been intensively investigated in the recent years, where Bouarissa and Boucenna [3] studied the electronic, optical and mechanical properties of AlAs and they showed that the results are in agreement with the availab le experimental and theoretical data. Chimata [4] studied theoretically the electronic structure of alu miniu m arsenide crystal, and they found that the band gap value obtained is in good agreement with the experimental value. Shimazaki and Asai[5] studied the energy band structure of Si, AlP, AlAs, Ga P and GaAs using screened Hartree-Fock exchange method, and they found that the direct and indirect band gaps don't agree with experimental values.…”
Section: Introductionsupporting
confidence: 53%
“…Therefore, alu min iu m arsenide has been intensively investigated in the recent years, where Bouarissa and Boucenna [3] studied the electronic, optical and mechanical properties of AlAs and they showed that the results are in agreement with the availab le experimental and theoretical data. Chimata [4] studied theoretically the electronic structure of alu miniu m arsenide crystal, and they found that the band gap value obtained is in good agreement with the experimental value. Shimazaki and Asai[5] studied the energy band structure of Si, AlP, AlAs, Ga P and GaAs using screened Hartree-Fock exchange method, and they found that the direct and indirect band gaps don't agree with experimental values.…”
Section: Introductionsupporting
confidence: 53%
“…A correlation between these two [43]; c ref [44]; d ref [34]; e ref [45]. fundamental properties has significant bearing on the band structure of semiconductors [36,46]. In this study, the fundamental energy band gap of the material of interest increases with increase in the composition x (see table 2), and n decreases with x (see table 4).…”
Section: Optical Propertiesmentioning
confidence: 72%
“…The behavior is monotonic. The trend is generally common for most of the III-V semiconductors [46][47][48] where the smaller band gap energy material has a larger value of n.…”
Section: Optical Propertiesmentioning
confidence: 94%